Hepatic steatosis associated with microsporidiosis in teleost fishes from Marajó Island, Brazil - MARCELA VIDEIRA; MICHELE VELASCO; PATRÍCIA MATOS; SÉRGIO C. DE SÃO CLEMENTE; OSIMAR SANCHES; PATRÍCIA SANTOS; EDILSON MATOS (Anais da Academia Brasileira de Ciências, 2014)
A total of 40 specimens of the teleost fish Gobioides grahamae Palmer & Wheeler, 1955 were obtained from the municipality of Salvaterra on Marajó Island in the Brazilian state of Pará. Their livers were removed and processed for light microscopy. Overall, 90% of the specimens presented some degree of steatosis of the liver, which was invariably associated with the presence of Microsporidium sp. The present study confirms the occurrence of steatosis in G. grahamae associated with parasitic infections by Microsporidium. The findings indicate that the condition of otherwise healthy fishes in their natural environment may be affected negatively by parasites.